Evaluación de la actividad antifúngica in vitro de extractos totales de dos especies vegetales como Ortiga y Hierba Mora contra el hongo Colletotrichum spp. aislado de tomate de árbol - Erazo Pozo, Andrea Estefania (2024)
This research focuses on the exploration of alternative and sustainable methods for the control of pathogens in agriculture. The main objective was to determine the effectiveness of total extracts of nettle (Urtica dioica) and blackberry (Solanum nigrum) in inhibiting the growth of the fungus Colletotrichum tamarilloi, a pathogen responsible for anthracnosis in the tree tomato. In this study, in vitro tests were carried out using serial concentrations of total plant extracts. The treatments were applied on petri dishes inoculated with C. tamarilloi, and mycelial growth was evaluated over a period of seven days. The results showed that the Nettle extract was more effective in inhibiting the growth of C. tamarilloi compared to the extract of Blackberry Grass. In particular, treatment with the highest concentration of Nettle extract (T1: 500 mg/ml) showed an inhibition percentage of 96.21% for day 4, while treatment with Blackberry Herb showed a maximum inhibition percentage of 90.27% under the same conditions. Chemical control (T6) was used as a reference, reaching 100% inhibition, which made it possible to compare the effectiveness of plant extracts. The statistical analysis showed that the differences between the treatments were highly significant, with p-values less than 0.0001, indicating that the variability observed in the inhibition is not random, but is directly associated with the treatments applied. The findings of this study suggest that both Nettle and Blackberry Grass have a high potential as biofungicides, offering a viable and sustainable alternative to traditional chemical fungicides. The implementation of these extracts could reduce the use of agrochemicals, promoting more sustainable and ecological agricultural practices.